2022
DOI: 10.1177/0261927x221116335
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Linguistic Shifts During Psychological Coping With the COVID-19 Pandemic

Abstract: How does language change reveal the psychological trajectories of people coping with a COVID-19 infection? This study examined writings on social media over 12 weeks from people who self-reported having tested positive for COVID-19. People used fewer words reflecting anxiety and distancing but more words indicating reinterpretation over time. The language patterns for describing the experience of COVID-19 infections differed from those for describing other unrelated topics. The findings reveal the temporal dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Unlike traditional analyses that describe topics through archetypal examples, topic modeling identifies topics based on how words are distributed in the documents and the extent to which the cluster of words leads to clear and coherent semantic meaning [28]. Previous work has applied topic modeling to various areas of sustainability, such as smart factories [29] and logistics [30], and has used a diverse set of datasets, including scientific literature [29], patent applications [30], and social media posts [31].…”
Section: Topic Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike traditional analyses that describe topics through archetypal examples, topic modeling identifies topics based on how words are distributed in the documents and the extent to which the cluster of words leads to clear and coherent semantic meaning [28]. Previous work has applied topic modeling to various areas of sustainability, such as smart factories [29] and logistics [30], and has used a diverse set of datasets, including scientific literature [29], patent applications [30], and social media posts [31].…”
Section: Topic Modelingmentioning
confidence: 99%
“…Then, the probabilities can be included in statistical models predicting outcomes of interest. Indeed, research beyond environmental science has demonstrated the utility of incorporating text-mining results into predictive modeling [31,50]. For example, text-mining results were found to improve the accuracy of machine learning models predicting information utility in online platforms [50].…”
Section: Theoretical and Practical Contributionsmentioning
confidence: 99%
See 1 more Smart Citation